Highly Regioselective and Diastereoselective, One‐Pot, Four‐Component Synthesis of Novel Spiroindenoquinoxalineindolizidine Derivatives. (28th May 2014) - Moemeni, Mehdi; Arvinnezhad, Hamid; Samadi, Saadi; Salahi, Farbod; Jadidi, Khosrow; Notash, Behrouz
<x xml:space="preserve">Abstract</x>